PENGARUH IKLAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN TAMU MENGINAP DI HOTEL MANHATTAN JAKARTA - Firdha Novianti; Parlagutan Silitonga (Eduturisma, 2016)
The competition among hotel industries in Jakarta is very tight. This is due to new establishment of hotels and other forms of accommodations during the last decade. Manhattan hotel in Kuningan Jakarta is a-5-star hotel that is really facing this tough competition, as it is close to many four and five- star-hotels. This research aimed to analyze the effect of independent variables, namely advertising and sales promotion, toward purchasing decision of customers (guests). The population are the guest for one month period and out of them are selected 100 samples, purposively, using accidental technique. While the analysis technique is using regression analysis. As a quantitative research where all prerequisite formula are applied, the tool is using SPSS for Windows ver. 20. The result shows that advertising and sales promotion significantly influenced the purchasing decision of customers. For further research, it is suggested to deploy other variables such as public relations, personal selling, and direct marketing.